THE MANAGEMENT ACCOUNTING IMPLEMENTATION STRATEGY TO IMPROVE MSME OPERATIONAL EFFICIENCY - Lestari, Dini Martinda; Kusumawati, Nugrahini (Yayasan Education and Social Center, 2024)
This research aims to analyze strategies for implementing management accounting in an effort to increase operational efficiency in Micro, Small and Medium Enterprises (MSMEs). The object of this research is Suka Drink Ratu Serang, an MSME in the beverage sector. A qualitative approach is used with interactive analysis to explore an in-depth understanding of the application of management accounting functions and factors. Primary data was obtained through unstructured interviews with the owner of Suka Drink Ratu Serang, while secondary data was used to provide further context. Direct observation techniques are applied to understand daily practices in the use of management accounting. Interviews and observations were carried out to obtain a representative picture. The results of this research indicate that the application of management accounting functions, including planning, organizing, directing, controlling and decision making, has a positive impact on the operational efficiency of MSMEs. The findings of this research can provide practical guidance for other MSMEs in optimizing management accounting strategies to improve their operational performance